2015
DOI: 10.2298/sarh1510584m
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of depression problems of adults who live in the security endangered territory

Abstract: To determine risk groups being in greater risk to suffer from depression is important for planning, enhancing, promoting and implementing the prevention strategies for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These nurses, therefore, were either experiencing burnout or at high risk of suffering it in the future. Urgency for further study of workplace hazards which are leading to burnout syndrome are supported by previously mentioned studies [25]. They also emphasis the priority of developing and improving interventions and therapies to prevent the above symptoms, in this manner helping nurses to cope with situations and circumstances that may lead to burnout syndrome [24].…”
Section: Plos Onementioning
confidence: 83%
“…These nurses, therefore, were either experiencing burnout or at high risk of suffering it in the future. Urgency for further study of workplace hazards which are leading to burnout syndrome are supported by previously mentioned studies [25]. They also emphasis the priority of developing and improving interventions and therapies to prevent the above symptoms, in this manner helping nurses to cope with situations and circumstances that may lead to burnout syndrome [24].…”
Section: Plos Onementioning
confidence: 83%
“…For respondents in the north of Kosovo and Metohija, the quality of life is often linked to refugee status (forced emigration from settlements south of the Ibar River, from Vučitrn, Svinjarе and other settlements). Mirković et al (2015) dealt with the problems of adults living in a securitythreatening area. The results in this study showed that problems with depression are significantly associated with female gender, older people, lower level of education, unemployment, poor financial situation and abuse.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO data from 2014, there are around 800,000 people annualy who commit suicide as a consequence of a spectrum of mental disorders [11,12]. Therefore, early detection of people at risk of mental disorders is of great importance in the prevention of mental disorders and suicide as a significant public health problem [11,13].…”
Section: Euthanasia and Assisted Suicide In People Suffering From Menmentioning
confidence: 99%